Table of Content - - (Journal of engineering sciences and information technology, 2024)
Table of Content:1. Al-Sulaymaniyah Tekkia as a station for Shami Pilgrimage during Ottoman Era (1516 AD-1918 AD)Eng. Amani Khalil Al-Rahhal2. The Blockchain Technology Applications and its Impact on Governance Performance: A Field Study on the Transportation Sector in PalestineDr. Maher Fuad Abu Farhah3. Evaluating the Impact of Artificial Intelligence in Managing Construction Engineering ProjectsMr. Abdullah Mohammad Abdelhamid Alhasan, Eng. Ebrahim Khaled Ebrahim Alawadhi4. Enhancing Object Detection Techniques Through Transfer Learning and Pre-trained ModelsAsst-Lecturer \ Ashwaq Katham Mtashre, Asst-Lecturer \ Dhakaa Mohsin Kareem, Asst-Lecturer \ Zainab Abd Al-Abbas Muhsen5. Network Classifier on Iris data Using MATLABAsst-Lecturer \ Jenan Jader Msaad, Lecturer \ Ruwaidah F.Albadri, Asst-Lecturer \ Alaa Majeed Shnin
Keywords: Journal of Engineering Sciences and Information Technology